SCREENING OF GASTRO-INTESTINAL TRACT‟S MALIGNANT NEOPLASMS - Tashtemirova, Olga; Rakhypbekov, Tolebay; Tashtemiro, Kamal; Dzhakova, Gulzhanat; Zhusupov, Sabit (European Scientific Journal, ESJ, 2014)
Screening of oncologic pathology of gastro-intestinal tract by means of multicenter endoscopic examination has shown that phylactic esophagogastroduodenoscopy, сolonofiberscopy can be recommended as an obligatory component during planned examination. Despite all the achievements of modern medicine , the entry of new methods of diagnosis and healing, the disease incidence and death rate due to oncologic diseases has been constantly increasing in the world. It is well-known , that cancer is the second leading reason of death after cardiovascular system diseases death. If to summarize the cancer frequency of all organs of gastro-intestinal tract, it will take the first place (more than 50%), powering past larynx cancer, breast cancer, and prostate cancer1. Therewith disease and death rate are the cancer of approximately all digestive systems 2. Numerous research proves, that disease prognosis mainly depends on oncology diagnose promptness, which gives much meaning to the earlier diagnosis. Unfortunately, 60– 80% patients with for the first time oncology diagnose already have III–IV stages of disease2. Potential causes of such late diagnose are late application of patients, erased clinical performance, and also deficient oncological suspicion of doctors with primary stage of healthcare.